2020
DOI: 10.1039/d0nr01638a
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-assisted mineralization of calcium phosphate: exploring confinement for the design of highly crystalline nano-objects

Abstract: Calcium phosphate mineralization is initiated through heterogenous enzymatic catalysis, resulting in the formation of highly ordered anisotropic nanostructures. The mineral phase features are modulated by physicochemical factors and confinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
(68 reference statements)
3
11
0
Order By: Relevance
“…The emergence of in vitro enzyme-assisted mineralization has motivated material scientists to explore ALP for the design of CaP-based materials with outstanding mechanical properties and bioactivity [120][121][122][123]. [118]). (B) Mechanism of the enzymatic process (adapted from [117]).…”
Section: Figure 3 (A)mentioning
confidence: 99%
See 3 more Smart Citations
“…The emergence of in vitro enzyme-assisted mineralization has motivated material scientists to explore ALP for the design of CaP-based materials with outstanding mechanical properties and bioactivity [120][121][122][123]. [118]). (B) Mechanism of the enzymatic process (adapted from [117]).…”
Section: Figure 3 (A)mentioning
confidence: 99%
“…In a recent article [ 118 ], we immobilized ALP enzymes within a multilayered film, using the sequential LbL technique, and showed the possibility to initiate CaP mineralization on the solid surface. Moreover, by combining real-time monitoring and ex situ characterization techniques, we observed that the growth mechanism of the mineral was significantly impacted by the physicochemical conditions of the medium (pH and temperature).…”
Section: Enzymatic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea has motivated the use of enzymes for the development of biomimetic systems, which may help to better understand the mechanism of biomineralization, , or for the design of biomaterials. In recent works, we have used tissue nonspecific alkaline phosphatase (ALP, EC 3.1.3.1) to initiate CaP mineralization in the homogeneous phase by generating, in situ, orthophosphate ions, which precipitate in the presence of calcium ions . This procedure was also successfully applied on solid surfaces, using immobilized enzymes, resulting in the formation of nanostructured mineralized layers . Interestingly, we observed that the degree of confinement influences the crystal phase.…”
Section: Introductionmentioning
confidence: 99%